Pelatihan Cerita Anak Budaya Lokal untuk Literasi Siswa bagi Guru Sekolah Dasar - Alwi, Nur Azmi; Kenedi, Ary Kiswanto; Ulya, Ridha Hasnul; Azizah, Zahratul; Mardin, Asna; Irwandi, Irwandi; Nadiroha, Widia; Fadira, Yaumi Aulia (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service program aimed to enhance elementary school teachers' capacity in developing and implementing culturally based children's stories as literacy media in the classroom. The background of this activity lies in the lack of contextual reading materials relevant to students’ cultural environment, particularly in IV Koto District, Agam Regency. The method consisted of training sessions, story development workshops, classroom implementation, and evaluation. Results showed a significant improvement in teachers’ ability to write and integrate local stories into thematic learning, alongside increased student enthusiasm for Minangkabau cultural narratives. The project produced 60 local children’s stories and integrated lesson plans. This program demonstrates that local-culture-based literacy strengthens students’ cultural identity and supports meaningful learning. The approach is recommended for replication in other regions with rich cultural heritage.